Delayed diagnosis and treatment of rheumatoid arthritis in Sarawak General Hospital - Sharifah Aishah, Wan; Cheng Lay, Teh; Yaw Kiet, Cheong; Ahmad Tirmizi, Jobli (Malaysian Medical Association, 2020)
Introduction: Rheumatoid arthritis (RA) is an autoimmune systemic inflammatory disorder characterised by symmetrical polyarthritis which leads to damage of joints if untreated. Early diagnosis and treatment of RA to achieve tight control of the disease will improve outcome and prevent disability. Objective: We aimed to examine the delays in the diagnosis of RA in patients presenting to the Rheumatology Unit, Sarawak General Hospital (SGH). Methods: Data on demographics and various delays were collected from the medical records from January 2015 until March 2018. Patient delay is defined as from the time onset of symptom to the first primary care presentation. Primary care delay is defined as from the first primary care presentation to referral to rheumatology. Rheumatology delay is defined as from rheumatology referral to appointment at the rheumatology clinic. Disease modifying anti-rheumatic drugs (DMARDS) delay is defined as from the rheumatology clinic appointment to starting DMARDS. Total delay is from symptom onset to starting DMARDS. Results: There were 84 new patients diagnosed with rheumatoid arthritis, out of which 66 were females (78.6%). The mean age was 54.1±12.0 years. Only 19 patients (22.6%) were treated with DMARDS within 12 weeks of symptom onset. The median time for patient delay was four weeks (Interquartile range (IQR) 2-20 weeks), while the median time primary care delay was 11 weeks (IQR 4-24 weeks). The median time for rheumatology delay was zero weeks (IQR 0- 1 week) and the DMARDS delay was zero week (IQR 0). The median time from symptom onset to DMARDS initiation was 23.5 weeks (IQR 13.25-51 weeks).